2016
DOI: 10.1093/jac/dkw046
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral drug transporters and metabolic enzymes in human testicular tissue: potential contribution to HIV-1 sanctuary site

Abstract: Our data suggest the testes are a complex pharmacological compartment that can restrict the distribution of certain antiretroviral drugs and potentially contribute to HIV-1 persistence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 55 publications
3
51
0
Order By: Relevance
“…HIV sequence diversity was measured as the APD at the indicated time points. Divergence was measured using a test for panmixia, with a P value of less than 0.001 considered significant after correcting for multiple comparisons (8), and by measuring the root-to-tip distances of sequences on phylogenetic trees (longer branches over time indicate viral evolution). A 1-sample t test was used to determine if there was a significant change in APD on ART, and a 2-tailed F test was used to determine whether the root-to-tip slopes were significantly different from 0.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HIV sequence diversity was measured as the APD at the indicated time points. Divergence was measured using a test for panmixia, with a P value of less than 0.001 considered significant after correcting for multiple comparisons (8), and by measuring the root-to-tip distances of sequences on phylogenetic trees (longer branches over time indicate viral evolution). A 1-sample t test was used to determine if there was a significant change in APD on ART, and a 2-tailed F test was used to determine whether the root-to-tip slopes were significantly different from 0.…”
Section: Resultsmentioning
confidence: 99%
“…There has been continued debate about whether the HIV reservoir is maintained through the persistence and proliferation of cells infected before the initiation of ART (1)(2)(3)(4)(5), or from ongoing viral replication in potential ART sanctuary sites, such as lymph nodes (LNs) (6)(7)(8)(9)(10), with subsequent trafficking of recently infected cells into the blood (10,11). If ongoing replication in tissues maintains the HIV reservoir, then preventing infection of new cells by developing antiretrovirals that better penetrate sanctuary sites such as LNs would be a high priority.…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have published data generated using both methods[28] , [12], however the utility of Western blot data is limited due to narrow dynamic range and often possible antibody cross reactivity. Further, relative gene expression data should be interpreted with caution, as the high sensitivity may lead to false positives.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups, including our own, have published studies evaluating the expression and localization of drug transporters in tissues relevant for HIV prevention[10], [11] and, more recently, cure[12]. However, there has been no consensus in the field on the optimal way to measure transporter expression.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that key ABC (ATP‐binding cassette) drug transporters, solute carrier transporters and cytochrome P450 metabolic enzymes (CYP3A4 and CYP2D6) previously shown to interact with many commonly used antiretroviral drugs are expressed at the mRNA and protein level in the testes of both subject groups and localize primarily at the blood‐testis barrier, with no significant differences between HIV and non HIV infected groups. They found that emtricitabine, lamivudine and tenofovir displayed favourable tissue penetration, reaching concentrations comparable to plasma levels and concluded that the testis can restrict the distribution of certain antiretroviral drugs and potentially contribute to HIV‐1 persistence .…”
Section: The Issue Of Inflammation and Immune Activationmentioning
confidence: 99%